PENGARUH ENVIRONMENTAL, SOCIAL AND GOVERNANCE, KINERJA KEUANGAN BANK DAN MAKROEKONOMI TERHADAP FINANCIAL DISTRESS - Nanda Apriliasari; Zulfa Irawati; Wiyadi Wiyadi; Muzakar Isa (LPPM Universitas Bina Bangsa, 2024)
This study aims to identify the impact of Enviromental, Social, and Governance (ESG), Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Cash Ratio, Debt to Asset Ratio (DAR), inflation and exchange rate on financial distress, using the X-Score model. This research used a quantitative approach, with secondary data. This research sample used purposive sampling and obtained four general banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The research was analyzed using a panel data regression model that will be tested using the E-Views version 10 software. The results of this study indicate that DAR has a significant positive effect on financial distress. However, ESG, NPL, CAR LDR, cash ratio, inflation, and exchange rates have no significant effect on financial distress